Education Empowerment: Bridging Academia and Community for Improved Learning and Dental Hygiene: Pemberdayaan Pendidikan: Menjembatani Akademisi dan Komunitas untuk Peningkatan Pembelajaran dan Kebersihan Gigi - Nurdiani, Ira; Putri, Nur Fransiska Maulidia; Nafisah, Eri; Prayoga, Bagas Adi; Yani, Muhammad (Proceedings of The ICECRS, 2023)
The aim of this service is to build cooperation between academics and the community to empower each other, especially in developing educational programs that focus on dental hygiene and providing counseling and education about dental hygiene to the community, increasing awareness of the importance of dental health. This service method works together with academics to create educational programs that suit the needs and characteristics of the community, taking into account innovation and interactive approaches. In addition, providing training to academics and volunteers from the community on effective dental hygiene teaching and counseling techniques. As a result of the community service, the community understands the importance of maintaining dental hygiene and practicing correct dental care. The benefits of community service are active participation in improving dental hygiene, creating a culture that cares about collective dental health. Highlight: Community-Academia Collaboration: The service fosters collaboration between academia and the community, tailoring dental hygiene programs to suit local needs, thereby promoting awareness and education on dental health. Interactive Educational Approach: Utilizing innovative and interactive methods in education ensures effective learning about dental hygiene, involving both academics and community volunteers in training for impactful teaching. Cultural Shift Towards Dental Health: The service creates a cultural shift by encouraging active participation, instilling a collective concern for dental health, and emphasizing the importance of proper dental care within the community. Keyword: Dental Hygiene, Education, Training